All the time in the world : new and selected stories - Doctorow, E. L., 1931-2015 (Random House, 2011)
Doctorow returns with a collection of short fiction about people who, as the author notes in his Preface, are somehow “distinct from their surroundings<U+2014>people in some sort of contest with the prevailing world”. Contains six stories that have never appeared in book form, and a selection of previous Doctorow classics.--Book jacket.